The Role Of Influencer Marketing In Increasing Brand Awareness Of Sambal Bakar Joeragan - Fauziah, Anesti Amelin; Ismail Yusup; Mira Nurfitriya (Jurnal Ekonomi, 2024)
Sambal Bakar Joeragan faces challenges in enhancing brand awareness due to low consumer awareness of the product caused by suboptimal marketing strategies. Influencer marketing was chosen as the focus of this study because it is considered one of the most effective approaches in the digital era for reaching a broader audience through the credibility and influence of social media personalities.  This research aims to provide an overview of influencer marketing and brand awareness and the impact of influencer marketing on Sambal Bakar Joeragan's brand awareness. The research method employed is quantitative, utilizing both descriptive and verification approaches. The research population consists of 944 Sambal Bakar Joeragan's Instagram followers. The sample determination uses Yount's formula with a sample size of 10% of the population, 94 respondents. The primary data used in this study were collected through questionnaires distributed and analyzed using simple linear regression analysis with the help of SPSS and through stages of validity tests, reliability tests, classical assumption tests, simple linear regression analysis, t-tests, and determination coefficient analysis. The study results indicate that influencer marketing positively impacts the brand awareness of Sambal Bakar Joeragan, with a determination coefficient contribution of 45.2%. These findings suggest that influencer marketing effectively increases brand awareness.